Evaluation of the microbial suitability of cereal flakes product (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the food label of some imported corn flakes products available in the local markets of the city of Baghdad. The results showed that the sign label for all trademarks contained information in Arabic and English (except for one sign in English only).